“QUE FALTA É ESSA?”: UMA ESCUTA DO LUGAR DAS PROFESSORAS SOBRE ALUNOS MEDICADOS NO ENSINO FUNDAMENTAL I. - Vieira, Cristiane Fogos (2020)
The purpose of this present study was to investigate teachers of a Municipal Elementary School I located in São Mateus / ES point of view regarding their relationship with medicalized students, as well as, at what place those who speak about them are at